Detection of Four Legume Viruses (AMV, CMV, BYMV, PSbMV) in One Multiplex RT-PCR Test Applied at ICARDA’s Seed Health and Virology Laboratory - Kumari, Safaa; Moukahel, Abdulrahman (International Center for Agricultural Research in the Dry Areas, 2024)
Many viruses have been reported affecting legume crops in West Asia and North Africa (WANA region), including Alfalfa mosaic virus (AMV, genus Alfamovirus, family Bromoviridae), Cucumber mosaic virus (CMV, genus Cucumovirus, family Bromoviridae), Bean yellow mosaic virus (BYMV) and Pea seed-borne mosaic virus (PSbMV) (genus Potyvirus, family Potyviridae). The nucleic acid of these four viruses is RNA and all are transmitted by aphids in a non-persistent manner and via seeds (including faba bean, lentil and chickpea), and pose a significant threat to the productivity of food and feed legume crops. Currently, virus detection methods rely primarily on serological tests such as ELISA and TBIA to detect viral infections. However, screening each sample for all viruses via individual virus-specific tests is both cost-prohibitive and labor-intensive. Additionally, antisera for some of these viruses are difficult to obtain. Thus, there is a clear need for a more efficient assay capable of detecting and differentiating the maximum number of these viruses in a single test, with high sensitivity to process large number of samples. The Reverse transcription polymerase chain reaction (RT-PCR) is a powerful technique for amplifying specific RNA sequences, enabling the detection of minute quantities of target molecules. Multiplex RT-PCR has been successfully applied to detect simultaneously different RNA viruses with high sensitivity. This report describes a validated molecular tool for a sensitive RT-PCR assay capable of detecting and identifying four legume viruses (AMV, CMV, BYMV, and PSbMV) in a single, straightforward test applied by ICARDA’s seed health and Virology Laboratory.